Direct determination of the collective pinning radius in the cuprate superconductor Bi2Sr2CaCu2O8+ δ - Dolz, Moira Ines; Kolton, Alejandro Benedykt; Pastoriza, Hernan (American Physical Society, 2010)
Fil: Dolz, Moira Ines. Comision Nacional de Energia Atomica. Gerencia del Area de Investigaciones y Aplicaciones no Nucleares. Gerencia de Fisica (CAB); Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina